Risk factors associated with Barrett's esophagus in hospitalized patients - Gómez, Gerard Martín (2020)
Objective: The objective of this article is to carry out a systematic review of scientific articles that reveal the risk factors associated with Barrett's esophagus in hospitalized patients. Methods: The review was performed by electronic search for articles related to risk factors associated with Barrett's esophagus in hospitalized patients. The PEO question was: What are the risk factors associated with Barrett's esophagus in hospitalized patients? The search sources were in PUBMED. The search terms were: Risk Factors; Barrett's esophagus; hospitalized patients. For this review, articles published from 2010 that had research experiences and theoretical-conceptual aspects were selected. Results: Of the 389 results found with indexing sources, a total of 25 articles were selected where 22 articles contained research results and 3 were considered for theoretical-conceptual aspects that are related to the purpose of the study. The search resulted in risk factors associated with Barrett's esophagus according to demographic characteristics and patient traits, presentation, and clinical data and lifestyles. Conclusion: An association of various risk factors with Barrett's esophagus is evidenced in hospitalized patients. The most concordant risk factors associated with Barrett's esophagus in the review were male sex, increased age, metabolic syndrome, hiatal hernia, use of proton pump inhibitors, gastroesophageal reflux (GER), obstructive sleep apnea, and erosive esophagitis.